Adubação com boro em batata-doce: efeito das fontes, doses e modos de aplicação - Echer, Fábio Rafael [UNESP]; Creste, Jose Eduardo (Universidade Estadual de Londrina (UEL), 2011)
Boron (B) fertilization can result in high yield and better sweet potato storage roots quality. However, there is few works about this subject. The objective was to evaluate the yield of sweet potato crops in response to B sources, rates and application form. The experimental design was complete randomized blocks, in factorial outline ((2x2x2)+1), with three replications, which resulted of the combination of sources of B (boric acid and borax), application form (via soil and via foliar) and doses of B (1 and 2 kg ha(-1)) and a control treatment (without B). There was no interaction between the factors studied for the commercial yield of sweet potato. No significant differences was found between B sources and application form, but they showed higher yield than the control treatment. Additionally, sweet potato yield increade with application of 2 kg ha(-1) of B.
Boron fertilization on sweet potato: effect of sources, rates and application form
Keywords: Ipomoea batatas; borax; boric acid; commercial productivity